Effects of Coaching and Mentoring on Employee Performance in the UK Hotel Industry - Neupane, Ramesh (International Journal of Social Sciences and Management, 2015)
This research aims to examine the effects of coaching and mentoring on Employee performance in the UK hotel industry. It also examines the extent of employee performance in association to coaching and mentoring; and examines the effects of coaching and mentoring on overall organisational performance. This study is based on cross-sectional method, deductive and quantitative approach. A sample of 172 managers and supervisors who have already worked as coach or mentors in the respective hotels are chosen by using convenience sampling technique. The survey strategy by using structured questionnaires was used for data collection. The collected data was analysed by using arithmetic mean, correlation, regression with the help of SPSS 20. This research confirmed that coaching and mentoring are positively correlated to employee performance and both factors have significant effect on employee performance. As the regression analysis shows that coaching has significant effects on overall employee performance as β = 0.466 and P = 0.007 which is less than 0.05. Similarly, mentoring has also significant effects on overall employee performance as β = 0.457, and P = 0.008 which is less than 0.05. Similarly, coaching and overall organisational performance are positively and significantly correlated as r = 0.707; and mentoring and overall organisational performance are also positively correlated as r = 0.456. The regression analysis shows that coaching has significant effects on overall organisational performance as β = 0.700 and P = 0.002 which is less than 0.05. But, mentoring has not significant effects on overall organisational performance as β = 0.010 and P = 0.961 which is greater than 0.05. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12323 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 123-138